IMMUNITY: TRADITIONAL ASSUMPTIONS AND NEW DATA ON THE IMMUNE RESPONSE FORMATION IN ONTOGENESIS - E.M. Bulatova; N.M. Bogdanova; T.V. Gabrusskaya; E.A. Lobanova-Dain (Union of pediatricians of Russia, 2008)
The article highlights the key issues of the classical immunology, modern definition of the immunity and immunologic tolerance, mechanisms of the specific and adaptive immune responses. Based on the data of the new scientific research, the authors showed peculiarities in the development of the immune system and anti contagious immune response in ontogenesis, the role of the breast feeding in the formation of an adequate immune response.Key words: immunologic reactivity, immune response, food allergy, cytokines, newborn, breast milk, breast milk oligosaccharides.